(untitled) (Research, Society and Development, 2025)
Malnutrition is a condition characterized by caloric, protein, vitamin, and mineral deficiencies resulting from poor nutrition. Its causes are varied, including food scarcity, disorders affecting food intake, malabsorption syndromes, and difficulties related to food preparation, especially among the elderly population. In this context, according to the Food and Agriculture Organization of the United Nations (FAO), there was an increase of 60 million undernourished people in 2019 compared to 2014, highlighting the persistence of this issue. This study aimed to estimate the incidence of hospitalizations due to malnutrition in the municipality of Cascavel between 2018 and 2023, describing the patient profile in terms of gender, age group, and ethnicity, and analyzing the characteristics of these hospitalizations, such as the average length of stay and number of deaths. To achieve this, a quantitative and descriptive study was conducted based on data collected from the DATASUS platform, in the “SUS Hospital Morbidity” section, selecting malnutrition among the ICD-10 morbidity options. The results indicated that female patients, of white ethnicity, and under 1 year of age were the most affected. Over the six years analyzed, 46 cases were recorded, with only 1 death due to malnutrition. Regarding the average length of hospital stay, the highest duration was recorded in 2018, with an average of 17.8 days.